2015
DOI: 10.1177/0004944115587917
|View full text |Cite
|
Sign up to set email alerts
|

How learning styles and preferences of first-year nursing and midwifery students change

Abstract: It is important that educators understand learning styles as an evolving individual characteristic. We investigate the changes in learning styles and preferences of first-year undergraduate nursing/midwifery students after six months of preliminary testing. Curry's 'onion ring model' proposes a stable inner 'Information processing' style (assessed by instruments such as Kolb Learning Style Inventory) compared to the outer 'Instructional preference' style (assessed by the VARK (Visual/Aural/Read-Write/Kinaesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 31 publications
1
16
0
7
Order By: Relevance
“…Like this study, other studies also found students whose learning style did not change. Mitchell, James and D'Amore [10] verified with version 7 of the VARK questionnaire and the Kolb LSI version 3.1 that 45% and 43% of the studied students, respectively, remained with the same learning style. However, their study does not contribute to an explanation as to why the students did not change or develop their learning repertoire.…”
Section: Hampering Factorsmentioning
confidence: 95%
See 3 more Smart Citations
“…Like this study, other studies also found students whose learning style did not change. Mitchell, James and D'Amore [10] verified with version 7 of the VARK questionnaire and the Kolb LSI version 3.1 that 45% and 43% of the studied students, respectively, remained with the same learning style. However, their study does not contribute to an explanation as to why the students did not change or develop their learning repertoire.…”
Section: Hampering Factorsmentioning
confidence: 95%
“…Educators need to encourage students to develop as a balanced learner, as espoused in Kolb's experiential learning theory. [10,24,25] Two Nordic studies highlighted the importance of students being aware of their strengths and shortcomings in learning and…”
Section: Expansion Of Learning Style Repertoirementioning
confidence: 99%
See 2 more Smart Citations
“…A different inventory, LSI questionnaire showed similar results with 45% of students remaining in the same learning modality and 55% of students changing. This research depicts dynamic changes within students" information processing and instructional preferences [16]. 5.…”
Section: Modality -Style/ Preference/ Strengthmentioning
confidence: 97%